TI_GERICHTE 52.2017.355 vom 16. November 2017 , Revoca della licenza di condurre. Durata minima della revoca in base allart. 16c cpv. 2 lett. d LCStr - TI Tribunale d'appello (2017)
Revoca della licenza di condurre. Durata minima della revoca in base all’art. 16c cpv. 2 lett. d LCStr